Difficulties in the recruitment of reminders and feminization in the skills of speaking and writing among non-Arabic speaking students in Brunei Darussalam - Bint Leaman, Nurliana (Journal of Humanities & Social Sciences, 2017)
This quantitative research was designed to diagnose and discuss the challenges faced by non-Arabic speakers in acquiring the rules of Arabic Gender and applying them in speaking and writing skills. The study was conducted in three Arabic schools in Negara Brunei Darussalam, distributed to (337) students. By using a descriptive analytical methodology through T-Test, the most important findings; there is a statistically significant relationship between the sex variable and the speaking skill, and due to this result, unfortunately the female student faced more difficulties rather than a male student and the best reason is crowded female student in the classroom, which led to difficulty dealing between teachers and student which affects the academic achievement, especially in language acquisition and its gender, as a result, failure applying Arabic Gender in their conversation.
Keywords: masculine; feminine; conversation; writing